Analisis Implementasi Model Bisnis On Demand Service Mobile Platform Terhadap Tingkat Kepuasan Pelanggan Gojek Di Indonesia - Alfian Nara Weking; Stefanus Ndala (Politeknik Harapan Bersama, 2018)
The influence of the role of technology today, bringing competition in the business world will be more stringent over time. Technology in the modern world is a very important role in supporting the company's business processes that will have a positive impact on the company. For example, business people in the field of transportation. PT. Gojek Indonesia is one of the online services transportation business that utilizes mobile technology platform to support the business process model on demand service used by Gojek companies so that the services provided to customers run well and in line with expectations of business opportunities in Indonesia. Gojek companies are examples of startup companies in Indonesia that use mobile platform technology. In this study using descriptive method that starts with a survey to find the necessary data such as the data downloader of the Gojek application in the play store and the reviews or comments given by the customer to the application. These data will then be analyzed to see the level of satisfaction of customers or users of mobile platform-based services.